2020
DOI: 10.1021/acs.macromol.9b02420
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oligo(oxyethylene) Moieties on Ion Conduction and Dielectric Properties of Norbornene-Based Imidazolium Tf2N Ionic Liquid Monomers

Abstract: Ion transport and segmental dynamics were studied for one- and two-armed norbornene ionic liquid monomers (ILMs) including imidazolium (Im+)-bis­(trifluoromethanesulfonyl)­imide (Tf2N–) pairs, with different imidazolium pendant structures containing either alkylene [(CH2)2] or oxyethylene [(OCH2CH2) x =(OE) x , x = 1, 2, or 3] units as the linkers between the norbornene and the imidazolium cation, using dielectric relaxation spectroscopy and oscillatory shear. All ILMs exhibit three dipolar relaxations, assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…Moreover, Choi et al observed that the addition of oligo (oxyethylene) (OE) linkers to (Im)(Tf 2 N) ILs lowered T g , accelerating the segmental α relaxation and the α 2 relaxation due to ions rearranging, and increased the static and Coulombic dielectric constants that were measured after the α and α 2 relaxations, respectively. 26 Furthermore, the β relaxation due to local OE-dipole motions was observed. An analysis of the three relaxation modes suggested that ion-pairing and OE-dipole motions substantially affect dielectric response in this electrolyte, through which ionic conductivity is strongly correlated with T g and the Coulombic dielectric constant.…”
Section: Towards Higher Ionic Conductivitymentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, Choi et al observed that the addition of oligo (oxyethylene) (OE) linkers to (Im)(Tf 2 N) ILs lowered T g , accelerating the segmental α relaxation and the α 2 relaxation due to ions rearranging, and increased the static and Coulombic dielectric constants that were measured after the α and α 2 relaxations, respectively. 26 Furthermore, the β relaxation due to local OE-dipole motions was observed. An analysis of the three relaxation modes suggested that ion-pairing and OE-dipole motions substantially affect dielectric response in this electrolyte, through which ionic conductivity is strongly correlated with T g and the Coulombic dielectric constant.…”
Section: Towards Higher Ionic Conductivitymentioning
confidence: 96%
“…The analysis of different counterions and chain lengths suggested that these parameters substantially alter T g , the extent of ionic aggregation, and the dielectric constant, and accordingly affect ion transport. Moreover, Choi et al observed that the addition of oligo (oxyethylene) (OE) linkers to (Im)(Tf 2 N) ILs lowered T g , accelerating the segmental α relaxation and the α 2 relaxation due to ions rearranging, and increased the static and Coulombic dielectric constants that were measured after the α and α 2 relaxations, respectively 26 . Furthermore, the β relaxation due to local OE‐dipole motions was observed.…”
Section: Surrounding Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chain growth polymerization (i) requires an IL monomer with an unsaturated or cyclic chemical structure that can be activated during the polymerization step ( Figure 5 ). Such a bond is often synthetically introduced into IL monomers (ILM) through the incorporation of methacrylic and methacrylamide [ 112 , 148 , 149 , 150 ], vinyl and styrene [ 116 , 151 , 152 , 153 , 154 , 155 ], or norbornene [ 156 , 157 , 158 ] or epoxy moieties. The sheer number of these reports demonstrates the applicability of this approach and underlines its advantages.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%